2010
DOI: 10.1111/j.1365-294x.2010.04867.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity‐fitness correlations of conserved microsatellite markers in Kentish plovers Charadrius alexandrinus

Abstract: Heterozygosity-fitness correlations (HFCs) are frequently used to examine the relationship between genetic diversity and fitness. Most studies have reported positive HFCs, although there is a strong bias towards investigating HFCs in genetically impoverished populations. We investigated HFCs in a large genetically diverse breeding population of Kentish plovers Charadrius alexandrinus in southern Turkey. This small shorebird exhibits highly variable mating and care systems, and it is becoming an ecological mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 83 publications
(249 reference statements)
3
44
0
Order By: Relevance
“…In addition, our work reveals novel insights into the distribution of a cosmopolitan superspecies of shorebird that has served as a model organism in evolutionary and ecological research (e.g. [15], [16], [17]). To fully resolve the root of the conflicting morphological and genetic data, future research will benefit from the incorporation of genome-wide sequences, from a focus on candidate loci for plumage pigmentation or from gene expression scans to characterize expression divergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our work reveals novel insights into the distribution of a cosmopolitan superspecies of shorebird that has served as a model organism in evolutionary and ecological research (e.g. [15], [16], [17]). To fully resolve the root of the conflicting morphological and genetic data, future research will benefit from the incorporation of genome-wide sequences, from a focus on candidate loci for plumage pigmentation or from gene expression scans to characterize expression divergence.…”
Section: Discussionmentioning
confidence: 99%
“…Here we investigate the evolutionary history of the White-faced Plover ( Charadrius alexandrinus dealbatus ), an enigmatic East Asian shorebird that is often thought to be a subspecies of the Kentish Plover ( C. alexandrinus ). C. alexandrinus is a widespread breeding resident of beaches and salt pans throughout northern temperate to subtropical latitudes that has served as a model organism in ecological and evolutionary research [15], [16], [17]. Recently, Küpper et al [18] restricted its range to the Old World by showing that American populations are not its sister and therefore must be considered an independent species, the Snowy Plover ( C. nivosus ).…”
Section: Introductionmentioning
confidence: 99%
“…To test for effects of heterozygosity associated with specific loci, we used likelihood ratio tests to compare models with a multilocus metric fitted as a linear expression against respective models with all 32 single loci fitted simultaneously as covariates (Küpper et al ., ; Szulkin et al ., ). Only if this test is significant should a single‐locus model be examined for loci with partial regression slopes significantly different from zero (Szulkin et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Many HFC studies have reported positive linear effects (Chapman et al ., ; Küpper et al ., ). Such positive effects may have been overrepresented due to publication bias (Coltman & Slate, ; bias may be diminishing – see Chapman et al ., ), biases arising from the properties of the genetic markers used (Küpper et al ., ), and because of a tendency for HFC studies to be conducted on small populations that have high inbreeding variance (see Coltman & Slate, ; Chapman et al ., ; Küpper et al ., ). The other end of the heterozygosity spectrum – negative HFCs – has received less attention (but see Szulkin & David, ).…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, there are logistical constraints to quantifying fitness based on lifetime reproductive success, and therefore one or more surrogate measures such as clutch size, sperm count, or seed production is most commonly used (e.g., [34]). Multilocus genotype data and fitness estimates can be combined to test for heterozygosity fitness correlations (HFCs), which occur when there is a correlation between overall heterozygosity and a measure of fitness; a positive HFC suggests that low heterozygosity is reducing fitness within a population.…”
Section: Adaptive Genes and Genetic Diversitymentioning
confidence: 99%